The High Five Model: Associations of the high factors with complete mental well-being and academic adjustment in university students - Castro Solano, Alejandro (2019)
Traditionally, models of positive personality traits have referred to moral characteristics. The High Five Model (HFM) is a factor model of individual positive traits based on an inductive psycho-lexical approach. Unlike other models, in the HFM the positive characteristics were freely determined by lay people, beyond any moral tones. The HFM comprises the following factors: erudition, peace, cheerfulness, honesty, and tenacity, known as ?the high factors.? This model was shown to positively exceed the capacity of normal personality to predict emotional, social, and psychological well-being. Additionally, this model is negatively associated with non-transmissible diseases, psychopathological symptoms, and psychopathological personality traits. This study aimed to increase the validation of the HFM, by analyzing the relationships among this model and positive mental health, psychopathological symptoms, academic adjustment, and academic performance in university students. Another objective was to study the association between complete mental well-being (i.e., high well-being and low psychopathological symptomatology) and the high factors of the HFM. The sample consisted of 256 university students. Correlations were calculated, and the two-step cluster analysis was used to obtain profiles. The results showed that tenacity and erudition high factors are positively associated with academic achievement and academic adjustment. Finally, each of the high factors was positively associated with complete mental well-being. The HFM has a broad scope, as it is related not only to psychological variables (e.g., well-being or psychopathological symptomatology) but also to academic performance (e.g., adjustment and achievement) in university students.